PENGARUH PENGGUNAAN ANTIKOAGULAN DAN TANPA ANTIKOAGULAN TERHADAP HASIL CROSSMATCHING - Reswari, Putu Ayu Dhana; Lentera Afrida Kusumawardani; Kwarta, Cityta Putri; Amalia, Yustisia; Widuri, Sasi (Rena Cipta Mandiri, 2026)
Pre-transfusion testing is a mandatory procedure to ensure compatibility between donor and recipient blood; therefore, the selection of sample type is a critical factor in determining the accuracy of test results. The use of blood samples with anticoagulant EDTA or without anticoagulant (serum) is suspected to influence crossmatching outcomes. This study aimed to analyze the effect of sample type on crossmatching results at the Blood Transfusion Unit of PMI Nunukan Regency. A pre-experimental study with a static group comparison design was conducted on 30 patient samples using a total sampling technique. Crossmatching examinations were performed using the gel test method and analyzed with the McNemar test. The results showed that all EDTA samples (100%) were incompatible, while serum samples showed 30% compatible and 70% incompatible results. Statistical analysis indicated a significant difference (p=0.000). It is concluded that the use of serum without anticoagulant is more recommended as it reduces false-positive reactivity and improves the efficiency of blood transfusion services.